Comparative cytogenetics of cichlid fishes through genomic in-situ hybridization (GISH) with emphasis on Oreochromis niloticus - Valente, Guilherme Targino [UNESP]; Schneider, Carlos Henrique; Gross, Maria Claudia; Feldberg, Eliana; Martins, Cesar [UNESP] (Springer, 2009)
Cichlidae is the most species-rich freshwater family of Perciformes and has attracted the attention of aquarium hobbyists, aquaculturists, and sport fisherman. Oreochromis niloticus is very important in aquaculture today and is currently used in varied areas of study as an 'experimental model'. Oreochromis niloticus has been characterized using classical and molecular cytogenetic techniques, with special attention paid to heterochromatin structure and the identification of sex chromosomes. In this study, we compare the genome of O. niloticus with that of other cichlids from Africa and South America using genomic in-situ hybridization (GISH). Our results show that at least some elements comprising the pericentromeric heterochromatin of Nile tilapia are species-specific and that the sequence of the majority of the long arm of the largest chromosome pair is conserved within the tilapiine group, which is composed of the genera Tilapia, Oreochromis, and Sarotherodon. It is suggested that the extensive regions of repeated DNA in the largest chromosome pair of O. niloticus resulted from chromosome rearrangement or accumulation caused by recombination suppression during the evolutionary history of the tilapiines.
Keywords: Cichlidae; Chromosome; Heterochromatin; Evolution; Repeated DNAs; Genome